Професійна реабілітація інвалідів як ефективний засіб їх інтеграції у суспільство - Терюханова, І.М. (Інститут демографії та соціальних досліджень НАН України, 2007)
В статье проанализирована система профессиональной реабилитации инвалидов в Украине и предложены направления её усовершенствования для ускорения процессов социальной и экономической интеграции инвалидов в общество, в том числе в сферу трудовых отношений. In the article the system of professional rehabilitation of the disabled in Ukraine has been made and the direction of its improvement aimed at accelerating of the processes of social and economic integration of the disabled into social environment as well as in labour relations have been offered.